Illocutionary Acts In The Movie Entitled All The Bright Places - Aurellia Cindy Elvinna; I Wayan Mulyawan; Nissa Puspitaning Adni (CV. Ulil Albab Corp, 2023)
This study is entitled “Illocutionary Acts in the Movie Entitled All the Bright Places. Two problems of study are formulated, specifically types of illocutionary acts used in the dialogue of the main characters in All the Bright Places movie and the context of situations used in the dialogue of the main characters in All the Bright Places Movie. The script of All the Bright Places movie served as the research data resource. This study used observation methods and note taking as a technique of collecting data. The steps of collecting data were to watch the movie, read the dialogue script in order to find the types of illocutionary acts and context of the situations of All the Bright Places movie, grouping the types of illocutionary acts and context of situations that were found in the movie script based on Searle’s (1979:12) theory and Leech’s (1983:6) theory. The findings show five types of illocutionary acts found in the dialogue of the main characters in All the Bright Places movie. From the analysis, there are data of representative illocutionary acts, data of directive illocutionary acts, data of expressive illocutionary acts, data of commissive illocutionary acts, and declarative illocutionary acts is not appearing any single time in the script of All the Bright Places movie. The purpose of context of situations is to consider the situational factors such as the speaker, the listener, the setting, and the cultural background, in order to accurately interpret the meaning of illocutionary acts in conversation.